Assessing the benefits of decentralised residential batteries for load peak shaving. (December 2020) - Jankowiak, Corentin; Zacharopoulos, Aggelos; Brandoni, Caterina; Keatley, Patrick; MacArtain, Paul; Hewitt, Neil
Highlights: A performance metric was developed to assess the benefits of load peak shaving. A photovoltaic and battery system for a test house in Northern Ireland was assessed. Peak Shaving management strategies help to shave peaks by 98%. To maximise the benefits of peak shaving a bigger battery size is needed. Peak shaving incentive tariff is necessary to justify the cost in larger batteries. Abstract: The deployment of distributed, behind-the-meter batteries operating on a peak-shaving mode, could benefit the electricity network, by providing optimal and location-specific services, increasing the penetration of intermittent renewable sources, and deferring costly network upgrades. However, the quantitative assessment of the benefits of load peak-shaving and its impact on the distribution network remains a challenge. The present paper introduces a metric of five indexes to evaluate the technical performances of load peak shaving. This metric is applied on a case study, based on a photovoltaic and battery system application for a test house in Northern Ireland, whose electricity demand is representative of the average UK demand profile. Two peak shaving strategies are compared with a more usual self-consumption mode, and the impact of the battery size is evaluated. Peak-shaving management strategies show promising performance by reducing peaks by more than 98%, while still decreasing the yearly consumption by 15%, and avoiding 75% of the photovoltaic-generated energy to be exported back to the grid. The economic analysis compared the net present values achieved under two different tariff policies. Using a peak-shaving incentivising tariff remunerating customers £0.24 per kWh of peak shaved allowed to maintain profitability with a capacity cost of up to £400/kWh, compared to only £150/kWh for a usual flat tariff scheme. Such an incentive is a step forward in promoting customers to purchase a larger battery and to operate it in a way that benefits the grid operator.